2014
DOI: 10.1007/s00265-014-1770-3
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone communication in ants: a detailed analysis of concentration-dependent decisions in three species

Abstract: The collective behavior of ants and the emergence of self-organizing patterns in ant colonies have been explained with various theoretical approaches based on models of trail following behavior elicited by pheromones. Although existing models can explain collective behavior of ants, there is little empirical evidence on how ants precisely respond to various pheromone concentrations. Thus, important knowledge is lacking about how much realistic description of ant behavior can be provided by the models and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 49 publications
3
53
0
Order By: Relevance
“…In other species, it has been shown that multiple pheromones can be selectively released by one or more glands to cope with different tasks (Jackson & Ratnieks, 2006), such as distinguishing between raid and emigration trails (Witte & Maschwitz, 2002), or to more quickly change trail direction when it is required by sudden environmental changes (Dussutour et al, 2009). Moreover, it appears that a signal can be changed by modulating the pressure of the gaster on the substrate and the pheromone concentration in the released droplet (Hangartner, 1969;Jackson & Châline, 2007;von Thienen, Metzler, Choe, & Witte, 2014). Finally, U-turn behaviour, also described in L. niger and M. pharaonis, might be involved and help orient the collective foraging towards the most rewarding resource (Beckers, Deneubourg, & Goss, 1992b;Hart & Jackson, 2006), although, in our study, we observed this behaviour only 13 times in total in our marking experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In other species, it has been shown that multiple pheromones can be selectively released by one or more glands to cope with different tasks (Jackson & Ratnieks, 2006), such as distinguishing between raid and emigration trails (Witte & Maschwitz, 2002), or to more quickly change trail direction when it is required by sudden environmental changes (Dussutour et al, 2009). Moreover, it appears that a signal can be changed by modulating the pressure of the gaster on the substrate and the pheromone concentration in the released droplet (Hangartner, 1969;Jackson & Châline, 2007;von Thienen, Metzler, Choe, & Witte, 2014). Finally, U-turn behaviour, also described in L. niger and M. pharaonis, might be involved and help orient the collective foraging towards the most rewarding resource (Beckers, Deneubourg, & Goss, 1992b;Hart & Jackson, 2006), although, in our study, we observed this behaviour only 13 times in total in our marking experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The new arm was either marked with a pheromone trail (treatments F-J) or not (treatments A-E). This pheromone trail was produced by immersing 8 worker hindgut glands in 2ml of dichloromethane (DCM), following von Thienen et al [42]. 5.6μl of this mixture was applied in an even line along the paper overlay covering the arm, using a capillary tube (Servoprax GmbH, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the presence of odours on a path affects pheromone deposition: while pheromone deposition on odourless paths is usually higher on the nestward journey (Beckers et al, 1993;Czaczkes and Heinze, 2015;Czaczkes et al, 2013Czaczkes et al, , 2016, pheromone deposition is higher on outward journeys on scented paths (this study, Czaczkes et al, 2018bCzaczkes et al, , 2018c. Finally, it should be noted that perception of pheromone, much like perception of quality, is also logarithmic (von Thienen et al, 2014), thus emphasising initial differences in pheromone concentration but damping out differences between strong trails. Nevertheless, it seems that colony-level decision-making effectively filters out the ants individual perceptual constrains (this study, Sasaki and Pratt, 2011), but the mechanism used to achieve this is still unknown.…”
Section: Risk Neutrality At the Colony Levelmentioning
confidence: 99%